An Analysis of the Church’s Responsibility on the Spiritual Nurture of Children: A Case Study of Alere Parish, Amuria Archdeaconry, Church of Uganda - Vicent Eyoku (Uganda Christian University, 2025)
This study analyzed the Church’s Responsibility in the Spiritual Nurture of Children: ACase Study of Alere Parish, Amuria Archdeaconry, Church of Uganda. The study was guided by the following objectives; to establish the role of the church in spiritual nurture of children in Alere Parish, to assess the challenges related to knowledge and skills among clergy and church leaders in the spiritual nurture of children in Alere Parish and to explore how collaborative efforts between parents and church leaders can enhance the effectiveness of children’s spiritual nurture in Alere Parish. The study adopted a case study research design and a qualitative approach. According to Creswell,J.W. (2013), Qualitative research is a type of research that focuses on exploring and understanding the meaning, experiences, and perspectives of individuals or groups1 The study revealed that in Alere Parish, the church utilized diverse strategies, such as Sunday School with age-appropriate lessons, storytelling, music, drama, and visual aids, to engage children and foster moral and spiritual growth. Programs like Children’s Day, monthly fellowships, bi-weekly meetings, and baptism/confirmation classes provide structured platforms for learning and community building. Parents were encouraged through seminars to be primary spiritual nurturers, aligning with Ephesians 6:4. Initiatives like Bible distribution and children’s choirs enhance Scripture access and faith expression. However, challenges include inadequate age-appropriate teaching materials, leading to reduced engagement when adult content is used.
Undergraduate Research